PENGARUH JENIS KELAMIN DAN LATAR BELAKANG SEKOLAH TERHADAP SIKAP TOLERANSI PERBEDAAN MAZHAB FIQH MAHASISWA BARU UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG TAHUN AKADEMIK 2011/2012 - Abbas Arfan, Ahmad Wahidi (lp2m-uin malang, 2011)
Conflicts between ethnic, religions, race and inter-community (SARA) especially between religion members in Indonesia is still going on. It gives image that religion tolerant between members is still low. In the fact, it is not only among different religion but also it is among one religion, especially Islamic member, like physically conflict between Sunni and Syi’ah in Bangil Jawa Timur 2010. So, it needs quantitative research to survey the tolerant value in checking the different mazhab fiqh especially for young generation as like student. So that the problems of this research are: (1) is there any relationship between gender in toleranting mazhab fiqh on the new students of The State Islamic University of Maulana Malik Ibrahim (Maliki) the academic year2011/2012? (2) is there any relationship between the difference of school background by toleranting mazhab fiqh on the new students of The State Islamic University of Maulana Malik Ibrahim (Maliki) the academic year 2011/2012?It is the type of quantitative method survey, data taking technique by non probability sampling-sistematis random sampling, research instrument by skala Likert model and data analisis technique with theta formulation tested with hypothesis chi-square test.The conclusion of this research are: (1) there is no significant relationship between gender in toleranting mazhab fiqh on the new students of The State Islamic University of Maulana Malik Ibrahim (Maliki) the academic year 2011/2012 (2) there is no significant relationship between the difference of school background by toleranting mazhab fiqh on the new students of The State Islamic University of Maulana Malik Ibrahim (Maliki) the academic year 2011/2012.Key words: relationship, tolerant in Fiqh thought, gender, school backgroun